Learning EU’s Roadmap to Consider ASEAN’s way - Phanphakdi, Waewpailin (วารสารปัญญาภิวัฒน์, 2013)
Abstract The Association of Southeast Asian Nations (ASEAN) is climbing to be the further level of economic competitiveness ratified a Charter as ASEAN Economic Community (AEC) with a single market in trade and production base. Since ASEAN is a new player of regional integration, ASEAN has been suggested to apply a roadmap of the European Union (the EU), the most effective economic integration, nowadays. However, there are a couple of big differences between the EU and ASEAN, probably indicate the unsuitability in adopting the EU’s way. The author accumulates critical details of both the EU and ASEAN with the criticisms to consider dim possibilities of the young institution of countries to follow the powerful giant’s path as an Economic Union, ranging from distinguishing forms of economic integration, illustrating their historical backgrounds and demonstrating other dissimilarities between the EU and ASEAN. Moreover, this article indicates some recommendations for ASEAN to handle with the coming, intensive changes as a result of becoming stronger AEC in 2015. Keywords: The Association of Southeast Asian Nations (ASEAN), The European Union (the EU), ASEAN Economic Community (AEC) and economic integration บทคัดย่อ สมาคมประชาชาติแห่งเอเชียตะวันออกเฉียงใต้ (อาเซียน) กำลังจะก้าวข้ามไปสู่การรวมตัวทางเศรษฐกิจในระดับที่สูงขึ้น ในนามของ ประชาคมเศรษฐกิจอาเซียน โดยมี หลักการของการเป็นตลาดและ แหล่งการผลิตร่วมในภูมิภาค อันเนื่องมาจากอาเซียนเสมือนเป็นเด็กใหม่ในการรวมตัวกันทางเศรษฐกิจ จึงเกิดคำแนะนำให้ประชาคมเศรษฐกิจอาเซียนประยุกต์ใช้แผนการดำเนินการของสหภาพยุโรป ซึ่งเป็นการรวมตัวทางเศรษฐกิจที่ประสบความสำเร็จมากที่สุดในปัจจุบัน อย่างไรก็ดี สหภาพยุโรปและอาเซียนมีข้อแตกต่างอยู่หลายประการ อันเป็นนัยสำคัญที่สื่อถึงความไม่เหมาะสมที่อาเซียนจะนำแผนและกลยุทธ์ในการรวมตัวกันทางเศรษฐกิจของสหภาพยุโรปมาประยุกต์ใช้ ผู้เขียนบทความวิชาการได้ทำการรวบรวมข้อมูลและเหตุปัจจัยที่สำคัญในการพิจารณาความเป็นไปได้ที่อาเซียนในฐานะน้องเล็กของการรวมตัวทางเศรษฐกิจ กับยักษ์ใหญ่แห่งอำนาจ อย่างเช่น สหภาพยุโรป นับตั้งแต่ การระบุให้เห็นความแตกต่างของการจัดตั้ง การรวมกลุ่ม ในแง่ของประวัติความเป็นมาของการจัดตั้ง และปัจจัยความแตกต่างอื่นๆ ที่สำคัญระหว่าสหภาพยุโรปและอาเซียน นอกจากนั้นผู้จัดทำยังได้ทำการระบุข้อแนะนำต่างๆในการรับมือกับความเปลี่ยนแปลงที่อาจจะเกิดขึ้นหลังการรวมตัวเป็นประชาคมทางเศรษฐกิจ เพื่อให้ภูมิภาคอาเซียนกลายเป็นประชาคมที่มั่นคงในปี ค.ศ.2015 ที่กำลังจะมาถึง คำสำคัญ: สมาคมประชาชาติแห่งเอเชียตะวันออกเฉียงใต้ (อาเซียน) สหภาพยุโรป ประชาคมเศรษฐกิจอาเซียน การรวมตัวกันทางเศรษฐกิจ